Investigation of Vilnius Upper Castle vertical deformations - Markelionis, Mindaugas; Miltinytė, Greta; Popovas, Darius; Aksamitauskas, Vladislovas Čelsovas (International Conference “Environmental Engineering”, 2017)
The aims of this study were to to review the monitoring methodology of the vertical deformations and to identify the reasons of deformations that occur in structures of Vilnius Upper Castle, Lithuania. Collected systemized data is processed with mathematical–statistical methods. In order to investigate the state of the buildings, a new cycle of measurements (XIV) was carried out in 2016. Data of all measurement cycles is presented and compared with previous data that was provided in technical reports of measurement cycles (first measurements began in 1968). In order to investigate conditions of the structures, data is presented graphically. When analyzing the graphics, it is possible to investigate changes of the buildings and possible causes of their appearance are presented. Long-term research and results have shown, that all the cracs and crevices that were found during monitoring (1968 to 2016) in Upper Castle’s structures were caused by large and uneven deformations.